Evaluation of Parathyroid Hormone and Vitamin D Levels among Surgery Outpatient Clinic Attendants in Shifa Medical Complex: A Cross-sectional Study - Alslaibi, Karam (International Journal of Innovative Research in Medical Science, 2024)
Background: Vitamin D and parathyroid hormone (PTH) play crucial roles in calcium homeostasis and bone metabolism. Understanding their levels and associations in the general population is essential for preventive and therapeutic interventions. Methods: A cross-sectional study was conducted to evaluate PTH and vitamin D levels among the general population. Data were collected over one year. A convenience sampling method was employed, and demographic information and laboratory results were obtained through standardized questionnaires and blood samples. Descriptive and inferential statistics were used for data analysis. Results: A total of 390 participants were included, with a predominance of females (65.9%). The mean age was 50.12 years, ranging from 8 to 89 years. Analysis of PTH levels revealed that 68.5% of participants had elevated levels (>65 pg/mL), while 26.4% had normal levels (15-65 pg/mL), and 5.1% had deficient levels (<15 pg/mL). Vitamin D deficiency was prevalent, with 17.2% severely deficient (<10 ng/mL) and 28.5% moderately deficient (10-15 ng/mL). A significant negative correlation was observed between vitamin D and PTH levels (p < 0.05), indicating higher PTH levels in individuals with severe vitamin D deficiency. Age was significantly associated with PTH levels (p < 0.05), with older individuals (>60 years) exhibiting higher mean PTH levels compared to younger age groups. Conclusion: This study highlights the high prevalence of vitamin D deficiency and its association with elevated PTH levels in the general population. The findings underscore the importance of monitoring and addressing vitamin D status, particularly in older individuals, to mitigate the risk of secondary hyperparathyroidism and related complications. Further research is needed to explore the underlying mechanisms and inform targeted interventions for optimizing vitamin D and PTH levels in diverse populations.